Hard carbon negative electrode material for sodium ion battery as well as preparation method and application of hard carbon negative electrode material
Through graphite microcrystal cross-linking technology, hard carbon negative electrode materials with high energy density and excellent electrochemical properties were prepared, which solved the problem of low energy density of hard carbon materials in the existing technology, and achieved high capacity and high pressure Density and high magnification performance.
Patent Information
- Application Number
- CN202411554771.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The existing hard carbon materials have low energy density in sodium ion batteries, making it difficult to take into account high capacity, high compaction density, high magnification and long-life performance.
Using graphite microcrystal crosslinked hard carbon material, the first carbon source is pre-carbonized, modified and high-temperature sintered to prepare carbon layer spacing of 0.37nm-0.40nm and Raman D/G(w) values. Hard carbon anode material in the range of 1.1-1.6.
The high capacity, high compaction density, high magnification and long-life performance of hard carbon materials is achieved, and the dynamic performance and cycle stability of sodium ion batteries are improved.
Smart Images

Figure CN119419265A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a hard carbon negative electrode material for sodium ion batteries and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries are similar to lithium-ion batteries in principle, have a good industrialization foundation, and are 30% to 40% cheaper than lithium batteries. In addition, sodium-ion battery raw materials are abundant, and are considered to be the most suitable secondary power source for lithium batteries. Hard carbon has the characteristics of cheap and easy to obtain raw materials, renewable, and a short process. It has long life, high power, and low temperature resistance, which can meet most application scenarios and is considered to be the most commercially promising sodium battery negative electrode material.
[0003] The main technical bottleneck facing hard carbon at present is its low energy density, and it is urgent to develop high-energy-density hard carbon products to meet market demand. Existing methods include pore-forming modification, doping modification, air oxidation modification, etc., but the carbon materials prepared by them often cannot take into account the high capacity, high compaction density, high rate and long life performance of hard carbon; among them, the existing pore-forming capacity-enhancing methods are difficult to accurately control the pore size, and cannot achieve both high capacity and high compaction density performance. Since the pore-forming agent is difficult to disperse evenly in the reaction system, the pore-forming reaction is uneven, resulting in a too wide pore size distribution of the carbon matrix. There will be some pores in the carbon matrix that have no sodium storage activity, resulting in a decrease in compaction density performance and volume-specific capacity. If the pore size is too large, some pore sodium storage sites will store sodium in the form of metallic sodium, increasing the risk of sodium precipitation, resulting in a decrease in rate and cycle performance. Doping modification can increase the sodium storage capacity of hard carbon, but it cannot take into account the cycle performance. The doping element combines with the hard carbon in the form of polar bonds, thereby forming defective sodium storage sites in the hard carbon matrix around the doping element. During the cycle, the non-polar chemical bonds will gradually break under the action of the external electric field, resulting in the inactivation of the defective sodium storage sites and a decrease in the cycle performance. Air oxidation modification is difficult to ensure the uniformity of the reaction. The oxygen component in the air often contacts the surface of the hard carbon material, and the oxygen inside the carbon matrix is less in contact, so the uniformity of the oxidation modification is difficult to ensure. Therefore, providing a high energy density hard carbon negative electrode material is an urgent problem to be solved. Summary of the invention
[0004] The main purpose of the present invention is to provide a hard carbon negative electrode material for sodium ion batteries and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] The embodiment of the present invention provides a hard carbon negative electrode material for a sodium ion battery, wherein the hard carbon negative electrode material for a sodium ion battery is a hard carbon material cross-linked with graphite microcrystals, and the carbon layer spacing of the hard carbon negative electrode material for a sodium ion battery is 0.37nm-0.40nm; the Raman D / G(w) value of the hard carbon negative electrode material for a sodium ion battery is in the range of 1.1-1.6; the 3T powder compaction density of the hard carbon negative electrode material for a sodium ion battery is 0.96g / cm 3 -1.10g / cm 3 .
[0007] The present invention also provides a method for preparing the aforementioned hard carbon negative electrode material for a sodium ion battery, which comprises:
[0008] Performing a first pre-carbonization treatment on a first carbon source to obtain a first precursor;
[0009] The first precursor is modified and then mixed with a reaction additive to obtain a second precursor; wherein the modification can at least enhance the reaction activity of amorphous carbon in the first precursor;
[0010] And, the second precursor is mixed with a second carbon source and subjected to a second pre-carbonization treatment and a high-temperature sintering treatment to obtain a hard carbon negative electrode material for a sodium ion battery.
[0011] The embodiment of the present invention also provides the use of the aforementioned hard carbon negative electrode material for sodium ion battery in the preparation of sodium ion battery.
[0012] An embodiment of the present invention further provides a sodium ion battery negative electrode sheet, which includes the aforementioned hard carbon negative electrode material for sodium ion battery.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The hard carbon negative electrode material for sodium ion batteries in the present invention has the characteristics of high cross-linking degree of graphite microcrystals (structural units of hard carbon), many closed pores, high carbon matrix density, and good conductivity. Therefore, it has the characteristics of high capacity, high compaction density, high rate and high cycle performance.
[0015] (2) The present invention pre-carbonizes the hard carbon material at a certain temperature to obtain the alternating distribution of crystallized carbon and amorphous carbon at the microscopic level, and modifies and chemically reacts to directionally etch the amorphous carbon of the first precursor, thereby preparing a second precursor with high crystallized carbon content, uniform pore distribution, small pore size and pores; then, a second carbon source is compounded, and the molecules of the second carbon source enter the pores of the hard carbon. After high-temperature sintering, the molecules of the second carbon source cross-link with the crystallized carbon, and the open pores are converted into closed pores, thereby obtaining a hard carbon negative electrode material with high graphite microcrystal cross-linking degree, many closed pores, high carbon matrix density and good conductivity. The closed pores serve as active sodium storage sites and contribute to capacity performance. High graphite microcrystal cross-linking degree and high conductivity are beneficial to improving kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 1 is a schematic diagram of a preparation process of a hard carbon negative electrode material for a sodium ion battery in a typical embodiment of the present invention;
[0018] Figure 2 is a SEM photograph of the hard carbon negative electrode material for sodium ion battery prepared in Example 1 of the present invention;
[0019] Figure 3 It is the first charge and discharge curve diagram of the hard carbon material in Example 1, Comparative Example 3, Comparative Example 6, and Comparative Example 8 of the present invention;
[0020] Figure 4a-4c Schematic diagrams of the pore structure of the second precursor in Example 1, Comparative Example 6, and Comparative Example 8 of the present invention respectively. DETAILED DESCRIPTION
[0021] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Specifically, as one aspect of the technical solution of the present invention, a hard carbon negative electrode material for a sodium ion battery is a hard carbon material cross-linked with graphite microcrystals, and the carbon layer spacing of the hard carbon negative electrode material for a sodium ion battery is 0.37nm-0.40nm; the Raman D / G(w) value of the hard carbon negative electrode material for a sodium ion battery is in the range of 1.1-1.6; the 3T powder compaction density of the hard carbon negative electrode material for a sodium ion battery is 0.96g / cm 3 -1.10g / cm 3 .
[0023] In some preferred embodiments, the Raman D / G(w) value of the hard carbon negative electrode material for sodium ion batteries is in the range of 1.2-1.5.
[0024] In some preferred embodiments, the powder conductivity of the hard carbon negative electrode material for sodium ion battery is 36S / cm-42S / cm.
[0025] In some preferred embodiments, the specific surface area of the hard carbon negative electrode material for sodium ion batteries is 1.0 m 2 / g-10.0m 2 / g.
[0026] In some preferred embodiments, the oil absorption of the hard carbon negative electrode material for sodium ion battery is 48 mL / 100 g-58 mL / 100 g.
[0027] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned hard carbon negative electrode material for a sodium ion battery, which comprises:
[0028] Performing a first pre-carbonization treatment on a first carbon source to obtain a first precursor;
[0029] The first precursor is modified and then mixed with a reaction additive to obtain a second precursor; wherein the modification can at least enhance the reaction activity of amorphous carbon in the first precursor;
[0030] And, the second precursor is mixed with a second carbon source and subjected to a second pre-carbonization treatment and a high-temperature sintering treatment to obtain a hard carbon negative electrode material for a sodium ion battery.
[0031] In some preferred embodiments, the preparation method specifically includes: performing a first pre-carbonization treatment on a first carbon source at 400°C-600°C in an inert gas atmosphere or an oxygen-deficient atmosphere, and then performing a first pulverization treatment on the obtained product to obtain a first precursor.
[0032] Further, the inert atmosphere includes any one or more combinations of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere, but is not limited thereto.
[0033] Furthermore, the oxygen-deficient atmosphere includes a gas atmosphere with an oxygen content of ≤1 wt%.
[0034] Furthermore, the first carbon source includes any one or more combinations of plant carbon sources, sugar carbon sources, resin carbon sources, and polymer carbon sources, but is not limited thereto.
[0035] Furthermore, the plant carbon source includes any one or more combinations of coconut shells, almond shells, pistachio shells, macadamia shells, date shells, chestnut shells, hazelnut shells, peanut shells, walnut shells, peach shells, cotton, wood, bamboo, bagasse, straw, and lignin, and is not limited thereto.
[0036] Furthermore, the carbohydrate carbon source includes any one or more combinations of sucrose, maltose, lactose, fructose, starch, and cellulose, but is not limited thereto.
[0037] Furthermore, the resin carbon source includes any one or more combinations of phenolic resin, polyimide resin, polyester resin, polyaldehyde resin, polyolefin resin, and polyacrylic resin, but is not limited thereto.
[0038] Furthermore, the polymer carbon source includes any one or more combinations of polyfurfuryl alcohol, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, natural rubber, and polyacrylonitrile, but is not limited thereto.
[0039] Furthermore, the first pre-carbonization treatment time is 0.5h-24h.
[0040] Furthermore, the preparation method specifically includes: using a pulverizing device to perform a first pulverizing treatment on the product obtained by the first pre-carbonization treatment until the median particle size is 1 μm-15 μm, and then sieving to obtain a first precursor.
[0041] In some preferred embodiments, the preparation method specifically comprises:
[0042] Modifying the first precursor by liquid phase modification to obtain a modified first precursor;
[0043] And, the modified first precursor is mixed with a reaction additive and reacted in an inert atmosphere at 500°C-700°C for 0.5h-3h, and then purified and dried to obtain a second precursor; wherein the inert atmosphere includes any one or more of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere. Further, the liquid phase modification includes: mixing the first precursor with an oxidizing acid solution and reacting at 50°C-100°C for 0.5h-24h to obtain a modified first precursor.
[0044] Furthermore, the oxidizing acid solution includes a solute and an acid, wherein the solute includes any one or more combinations of potassium permanganate, potassium dichromate, potassium perchlorate, potassium hypochlorite, sodium permanganate, sodium dichromate, sodium perchlorate, sodium hypochlorite, and hydrogen peroxide; the acid includes any one or more combinations of hydrochloric acid, hydrofluoric acid, phosphoric acid, sulfuric acid, and nitric acid, and the concentration of the solute in the oxidizing acid solution is 0.1wt%-5wt%.
[0045] Furthermore, the mass ratio of the first precursor to the oxidizing acid solution is 1:2-20.
[0046] Furthermore, the mass ratio of the reaction additive to the modified first precursor is 0.05-2.0:1.
[0047] Further, the reaction additive includes any one or more combinations of iron oxide, ferroferric oxide, magnesium oxide, calcium oxide, zinc oxide, chromium oxide, silver oxide, niobium oxide, cobalt oxide, nickel oxide, and copper oxide, but is not limited thereto.
[0048] In some preferred embodiments, the preparation method specifically comprises:
[0049] The second precursor and the second carbon source are fully mixed, and then the obtained mixture is subjected to a second pre-carbonization treatment at 400°C-600°C in an inert atmosphere, and then the obtained product is subjected to a second pulverization treatment to obtain a second pulverized material; and, in an inert atmosphere, the second pulverized material is subjected to high-temperature sintering at 1200°C-1500°C for 0.5h-10h to obtain a hard carbon negative electrode material for a sodium ion battery; wherein the inert atmosphere includes any one or more combinations of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere.
[0050] Furthermore, the second carbon source includes a carbon source with a residual carbon rate lower than 15 wt %.
[0051] Furthermore, the second carbon source includes any one or more combinations of glucose, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyvinyl alcohol, epoxy resin, urea-formaldehyde resin, and melamine resin, but is not limited thereto.
[0052] Furthermore, the mass ratio of the second carbon source to the second precursor is 0.03-0.3:1.
[0053] Furthermore, the second pre-carbonization treatment time is 0.5h-24h.
[0054] Furthermore, the preparation method specifically comprises: using a pulverizing device to perform a second pulverizing treatment on the product obtained by the second pre-carbonization treatment until the median particle size is 1 μm-15 μm, and then sieving to obtain a second pulverized material.
[0055] In some more specific embodiments, the preparation process diagram of the method for preparing the hard carbon negative electrode material for sodium ion battery is as follows Figure 1 As shown, it includes:
[0056] (1) performing a first pre-carbonization and a first pulverization on a first carbon source to obtain a first precursor;
[0057] (2) modifying the first precursor, mixing it with a reaction additive, performing a chemical reaction, purifying and drying it, and obtaining a second precursor;
[0058] (3) The second precursor is mixed with the second carbon source, and subjected to second pre-carbonization, second pulverization, and high-temperature sintering to obtain a hard carbon negative electrode material for a sodium ion battery.
[0059] Preferably, in step (1), the first carbon source comprises one or a combination of at least two of a plant carbon source, a sugar carbon source, a resin carbon source, and a polymer carbon source; wherein the plant carbon source is one or a combination of at least two of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, chestnut shell, hazelnut shell, peanut shell, walnut shell, peach shell, cotton, wood, bamboo, bagasse, straw, and lignin; the sugar carbon source comprises one or a combination of at least two of sucrose, maltose, lactose, fructose, starch, and cellulose; the resin carbon source comprises one or a combination of at least two of phenolic resin, polyimide resin, polyester resin, polyaldehyde resin, polyolefin resin, and polyacrylic acid resin; the polymer carbon source comprises one or a combination of at least two of polyfurfuryl alcohol, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, natural rubber, or polyacrylonitrile.
[0060] Preferably, the temperature of the first pre-carbonization is 400°C-600°C, the holding time is 0.5-24h, and the carbonization atmosphere is an inert gas atmosphere or an oxygen-deficient atmosphere; the inert atmosphere is any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two of them; the oxygen-deficient atmosphere is a closed space atmosphere that isolates gas from entering.
[0061] Preferably, the first crushing step includes: crushing the material obtained from the first pre-carbonization to a median particle size of 1 μm-15 μm, and sifting through a 30-mesh sieve; the crushing equipment is one of a ball mill, a jet mill, a mechanical crusher, and a roller mill, or a combination of at least two of them.
[0062] Preferably, the modification reaction in step (2) comprises: subjecting the crushed material obtained in step (1) to liquid phase modification.
[0063] Furthermore, the liquid phase modification comprises: putting the first precursor obtained in step (1) into a certain oxidizing acid solution, heating to 50°C-100°C, reacting for 0.5h-24h, cooling, solid-liquid separation, washing, and drying to obtain the modified material. The solute of the oxidizing solution comprises any one of potassium permanganate, potassium dichromate, potassium perchlorate, potassium hypochlorite, and hydrogen peroxide, or a combination of at least two thereof, and the acid comprises any one of hydrochloric acid, phosphoric acid, sulfuric acid, and nitric acid, or a combination of at least two thereof.
[0064] Preferably, the chemical reaction in step (2) comprises: mixing the modified material and the reaction additive in a certain mass ratio (the mass ratio of the chemical reactant to the modified material is 0.05-2:1), heating to 500°C-700°C, keeping the temperature for 0.5h-3h, and cooling to room temperature.
[0065] Preferably, the reaction additive is any one of iron oxide, ferroferric oxide, magnesium oxide, calcium oxide, zinc oxide, chromium oxide, silver oxide, niobium oxide, cobalt oxide, nickel oxide, and copper oxide, or a combination of at least two thereof.
[0066] Preferably, the specific method of purification in step (2) is: mixing the material obtained by the chemical reaction, acid and water in a certain proportion, stirring for 0.5h-24h, solid-liquid separation, washing to a pH value of 4-8, and drying; the acid is one of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid, or a combination of at least two thereof.
[0067] Preferably, the specific method of step (3) includes: adding the second carbon source and the second precursor into a VC machine at a mass ratio of 0.03-0.3:1 and mixing for 10 min-60 min, wherein the second carbon source is a carbon source with a residual carbon content of less than 15%, including any one of glucose, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyvinyl alcohol, epoxy resin, urea-formaldehyde resin, and melamine resin, or a combination of at least two thereof.
[0068] Preferably, the second pre-carbonization is carried out under the same conditions as the first pre-carbonization.
[0069] Preferably, the second pulverizing condition includes: pulverizing the material obtained from the pre-second carbonization to a median particle size of 1 μm-15 μm, and sieving through a 30-mesh sieve; the pulverizing equipment is one of a ball mill, a jet mill, a mechanical pulverizer, and a roller mill, or a combination of at least two of them.
[0070] Preferably, the high-temperature sintering conditions include: transferring the second crushed material to a certain sintering equipment, heating it to 1200°C-1500°C under an inert gas atmosphere, keeping it at this temperature for 0.5h-10h, and cooling it naturally; the sintering gas atmosphere is an inert gas atmosphere; the inert atmosphere is any one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere, or a combination of at least two of them; the sintering equipment includes one of a tubular furnace, a box furnace, a roller kiln, and a tunnel kiln, or a combination of at least two of them.
[0071] Preferably, after high-temperature sintering, the VC is dispersed and screened; the mesh number of the screening screen is 200-325 meshes.
[0072] The hard carbon material of the present invention has both high capacity and high compaction performance. The present invention performs a first pre-carbonization on a first carbon source to obtain a first precursor composed of crystallized carbon and amorphous carbon; after a modification reaction, the reaction activity of amorphous carbon is greatly improved, while the reaction activity of crystallized carbon is slightly improved, and the degree of difference in the reaction activities of the two increases; a reaction additive is mixed, and the first precursor and the reaction additive undergo a chemical reaction, the amorphous carbon is significantly etched, and the crystallized carbon is largely retained; then a second carbon source is mixed and a second pre-carbonization is performed, and the second carbon source at least partially penetrates into the second precursor; after a second pre-carbonization and high-temperature sintering, a hard carbon material is obtained; this hard carbon material has a large number of pore sodium storage sites with sodium storage activity, and some inactive open pores are filled with the second carbon source, so it has excellent capacity and compaction performance; amorphous carbon is the reason that hinders the three-dimensional cross-linking of crystallized carbon, and through chemical reaction, the amorphous carbon is directionally etched, and the second carbon source is compounded on this basis, which is beneficial to improving the three-dimensional cross-linking degree between graphite crystallites, further promoting the conversion of open pores into closed pores, increasing closed pore sodium storage sites, improving the density of carbon materials, and improving compaction density performance.
[0073] Another aspect of an embodiment of the present invention further provides use of the aforementioned hard carbon negative electrode material for sodium ion batteries in the preparation of sodium ion batteries.
[0074] Another aspect of an embodiment of the present invention further provides a sodium ion battery negative electrode sheet, which includes the aforementioned hard carbon negative electrode material for a sodium ion battery.
[0075] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0076] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0077] Example 1
[0078] (1) In a nitrogen atmosphere, the coconut shell is kept at 500° C. in a box furnace for 24 h, then crushed by a jet mill to a median particle size of about 5 μm, and sieved through a 30-mesh sieve to obtain a first precursor;
[0079] (2) Add 2 parts of hydrogen peroxide (31wt%) and 4 parts of concentrated hydrochloric acid (35wt%) to 10 parts of pure water in sequence, stir evenly, and prepare a 4.5wt% hydrogen peroxide hydrochloric acid solution. The first precursor obtained in step (1) is put into 2 times the weight of the above hydrogen peroxide hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6h, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micron-sized iron oxide powder are mixed in a mass ratio of 1:0.5, heated to 950°C in a box furnace under a nitrogen atmosphere, kept warm for 2h, cooled to room temperature, and the material obtained by the chemical reaction, hydrochloric acid, and 60°C pure water are mixed in a certain ratio (1:0.5:3), stirred for 10h, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor;
[0080] (3) Put polystyrene and the second precursor in a mass ratio of 0.1:1 into a VC machine and mix for 30 minutes. Then, in a nitrogen atmosphere, pre-carbonize the obtained mixture at 600°C in a box furnace for a second time, keep it warm for 0.5 hours, and then use a jet mill to grind it to a median particle size of about 5μm, sieve it through a 30-mesh screen, and obtain a second crushed material; finally, transfer the second crushed material to a box furnace, heat it to 1200°C in a nitrogen atmosphere, keep it warm for 4 hours, and cool it naturally to obtain a hard carbon negative electrode material for sodium ion batteries. The SEM photo of the hard carbon negative electrode material for sodium ion batteries prepared in this embodiment is shown in FIG. Figure 2 As shown, the first charge and discharge curve is as follows Figure 3 The schematic diagram of the pore structure of the second precursor is shown in Figure 4a shown.
[0081] Example 2
[0082] (1) In an oxygen-deficient atmosphere, sucrose is kept at 600° C. in a push plate kiln for 2 h, then crushed by a jet mill to a median particle size of about 3 μm, and sieved through a 30-mesh sieve to obtain a first precursor;
[0083] (2) Add 1 part of potassium permanganate and 9 parts of hydrofluoric acid (40wt%) to 90 parts of pure water in sequence by mass, stir evenly, and prepare a 1wt% potassium permanganate hydrofluoric acid solution. The first precursor obtained in step (1) is put into 20 times the weight of the above potassium permanganate hydrofluoric acid solution, heated to about 80°C in a water bath under stirring, reacted for 24 hours, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micron-sized magnesium oxide powder are mixed in a mass ratio of 1:0.05, heated to 700°C in a box furnace under an argon atmosphere, kept warm for 0.5h, cooled to room temperature, the material obtained by the chemical reaction, sulfuric acid (20wt%), and 60°C pure water are mixed in a certain ratio (1:1:10), stirred for 3h, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor;
[0084] (3) The solid epoxy resin and the second precursor were put into a VC machine at a mass ratio of 0.03:1 and mixed for 20 minutes. After that, the obtained mixture was pre-carbonized at 400°C in a box furnace in a helium atmosphere and kept warm for 24 hours. Then, it was crushed by a jet mill to a median particle size of about 4 μm, and sieved through a 30-mesh sieve to obtain a second crushed material. Finally, the second crushed material was transferred to a tubular furnace, heated to 1500°C in a neon atmosphere and kept warm for 4 hours, and naturally cooled to obtain a hard carbon negative electrode material for sodium ion batteries.
[0085] Example 3
[0086] (1) In a helium atmosphere, the phenolic resin is kept at 550° C. for 4 h in a roller kiln, then crushed by a jet mill to a median particle size of about 15 μm, and sieved through a 30-mesh sieve to obtain a first precursor;
[0087] (2) Add 0.1 parts of sodium hypochlorite and 9.9 parts of sulfuric acid (30 wt%) to 90 parts of pure water in sequence, stir evenly, and prepare a 0.1 wt% sodium hypochlorite sulfuric acid solution. The first precursor obtained in step (1) is added to 2 times the weight of the above sodium hypochlorite sulfuric acid solution, heated to about 100°C in a water bath under stirring, reacted for 0.5 hours, and cooled to obtain a modified first precursor. Then, the modified first precursor and micron-sized silver oxide powder are mixed in a mass ratio of 1:2, heated to 1000°C in a box furnace under a neon atmosphere, kept warm for 1 hour, cooled to room temperature, and the obtained chemical reaction material, nitric acid (50 wt%) (31 wt%), and 70°C pure water are mixed in a certain ratio (1:0.5:5), stirred for 6 hours, solid-liquid separation, washed to pH = 5-6, and dried to obtain a second precursor;
[0088] (3) PVA powder and a second precursor were placed in a VC machine at a mass ratio of 0.3:1 and mixed for 30 minutes. The mixture was then pre-carbonized at 500°C in a box furnace in a nitrogen atmosphere for 4 hours. The mixture was then crushed to a median particle size of about 6 μm using a jet mill and sieved through a 30-mesh sieve to obtain a second crushed material. Finally, the second crushed material was transferred to a sintering furnace, heated to 1250°C in a neon atmosphere and kept for 3 hours, and then naturally cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0089] Example 4
[0090] (1) In a nitrogen atmosphere, polyaniline was kept at 500° C. in a box furnace for 3 h, then crushed by a jet mill to a median particle size of about 6 μm, and sieved through a 30-mesh sieve to obtain a first precursor;
[0091] (2) Add 3 parts of potassium dichromate and 7 parts of hydrochloric acid (40wt%) to 90 parts of pure water in sequence, stir evenly, and prepare a 3wt% potassium dichromate hydrochloric acid solution. The first precursor obtained in step (1) is added to 5 times the weight of the above potassium dichromate hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6 hours, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micron-sized niobium oxide powder are mixed in a mass ratio of 1:1, heated to 500°C in a box furnace under a krypton atmosphere, kept warm for 1 hour, cooled to room temperature, and the material obtained by the chemical reaction, nitric acid (50wt%), and 60°C pure water are mixed in a certain ratio (1:0.2:10), stirred for 6 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor;
[0092] (3) The polytetrafluoroethylene powder and the second precursor were put into a VC machine at a mass ratio of 0.15:1 and mixed for 60 minutes. After that, the obtained mixture was pre-carbonized at 550°C in a box furnace in a nitrogen atmosphere and kept warm for 10 hours. Then, it was crushed to a median particle size of about 5 μm using a jet mill and sieved through a 30-mesh sieve to obtain a second crushed material. Finally, the second crushed material was transferred to a sintering furnace, heated to 1300°C in a nitrogen atmosphere and kept warm for 3 hours, and naturally cooled to obtain a hard carbon negative electrode material for sodium ion batteries.
[0093] Example 5
[0094] (1) In a helium atmosphere, bamboo powder was kept at 400° C. in a box furnace for 3 h, then ground into a median particle size of about 1 μm using a jet mill, and sieved through a 30-mesh sieve to obtain a first precursor;
[0095] (2) Add 3 parts of potassium hypochlorite and 7 parts of hydrochloric acid (40wt%) to 90 parts of pure water in sequence, stir evenly, and prepare a 3wt% potassium hypochlorite hydrochloric acid solution. The first precursor obtained in step (1) is added to 15 times the weight of the above potassium hypochlorite hydrochloric acid solution, heated to about 70°C in a water bath under stirring, reacted for 24 hours, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micron-sized cobalt oxide powder are mixed in a mass ratio of 1:0.8, heated to 650°C in a box furnace under an argon atmosphere, kept warm for 2 hours, cooled to room temperature, and the obtained chemical reaction material, hydrochloric acid, and 80°C pure water are mixed in a certain ratio (1:0.8:10), stirred for 3 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor;
[0096] (3) Urea-formaldehyde resin and the second precursor were put into a VC machine at a mass ratio of 0.25:1 and mixed for 15 minutes. The mixture was then pre-carbonized at 600°C in a box furnace in a nitrogen atmosphere for 3 hours. The mixture was then crushed to a median particle size of about 2 μm using a jet mill and sieved through a 30-mesh sieve to obtain a second crushed material. Finally, the second crushed material was transferred to a tubular furnace, heated to 1350°C in a nitrogen atmosphere and kept for 6 hours, and then naturally cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0097] Example 6
[0098] (1) In a krypton atmosphere, a polyaldehyde resin is kept at 500° C. in a tube furnace for 10 h, then ground by a jet mill to a median particle size of about 12 μm, and sieved through a 30-mesh sieve to obtain a first precursor;
[0099] (2) Add 2 parts of sodium hypochlorite and 8 parts of hydrochloric acid (40wt%) to 90 parts of pure water in sequence, stir evenly, and prepare a 2wt% sodium hypochlorite hydrochloric acid solution. The first precursor obtained in step (1) is added to 3 times the weight of the above sodium hypochlorite, heated to about 65°C in a water bath under stirring, reacted for 3 hours, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micron-sized silver oxide powder are mixed in a mass ratio of 1:0.5, heated to 950°C in a box furnace under a helium atmosphere, kept warm for 1 hour, cooled to room temperature, and the material obtained by the chemical reaction, nitric acid (50wt%), and 80°C pure water are mixed in a certain ratio (1:0.2:10), stirred for 12 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor;
[0100] (3) Polyvinyl alcohol and the second precursor were put into a VC machine at a mass ratio of 0.3:1 and mixed for 15 minutes. Then, the obtained mixture was pre-carbonized at 500°C in a box furnace in a helium atmosphere for 4 hours, and then crushed to a median particle size of about 15 μm using a jet mill, and sieved through a 30-mesh sieve to obtain a second crushed material; finally, the second crushed material was transferred to a tubular furnace, heated to 1250°C in a helium atmosphere, and kept warm for 10 hours, and naturally cooled to obtain a hard carbon negative electrode material for sodium ion batteries.
[0101] Example 7
[0102] (1) In an oxygen-deficient atmosphere, polyacrylonitrile was kept at 450° C. in a box furnace for 6 h, then crushed by a jet mill to a median particle size of about 8 μm, and sieved through a 30-mesh sieve to obtain a first precursor;
[0103] (2) Add 1 part of sodium hypochlorite and 9 parts of hydrochloric acid (40wt%) to 90 parts of pure water in sequence, stir evenly, and prepare a 1wt% sodium hypochlorite hydrochloric acid solution. The first precursor obtained in step (1) is added to 2 times the weight of the above sodium hypochlorite, heated to about 100°C in a water bath under stirring, reacted for 0.5h, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micron-sized calcium oxide powder are mixed in a mass ratio of 1:0.3, heated to 650°C in a box furnace under a krypton atmosphere, kept warm for 2h, cooled to room temperature, and the obtained chemical reaction material, hydrochloric acid, and 80°C pure water are mixed in a certain ratio (1:0.5:4), stirred for 7h, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor;
[0104] (3) Urea-formaldehyde resin and the second precursor were put into a VC machine at a mass ratio of 0.25:1 and mixed for 20 minutes. The mixture was then pre-carbonized at 450°C in a box furnace in a nitrogen atmosphere for 8 hours. The mixture was then crushed to a median particle size of about 6 μm using a jet mill and sieved through a 30-mesh sieve to obtain a second crushed material. Finally, the second crushed material was transferred to a tubular furnace, heated to 1400°C in a helium atmosphere and kept for 2 hours, and then naturally cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0105] Comparative Example 1
[0106] The method is the same as that of Example 1, except that the temperature condition of the first pre-carbonization in step (1) is changed to "800° C. for 24 hours".
[0107] Comparative Example 2
[0108] The method is the same as that of Example 1, except that the temperature condition of the first pre-carbonization in step (1) is changed to "350° C. for 24 hours".
[0109] Comparative Example 3
[0110] The method is the same as Example 1, except that in step (2), the first precursor is not modified or chemically reacted, and in step (3), the second carbon source is not compounded; that is:
[0111] (2) mixing the first precursor obtained in step (1), hydrochloric acid, and 60° C. pure water in a certain ratio (1:0.5:3), stirring for 10 h, separating the solid and the liquid, washing to a pH of 5-6, and drying to obtain a second precursor;
[0112] (3) The second precursor was transferred to a box furnace, heated to 1200°C in a nitrogen atmosphere for 4 hours, and cooled naturally to obtain a hard carbon negative electrode material for a sodium ion battery. The first charge and discharge curve of the material in this comparative example is shown in FIG. Figure 3 shown.
[0113] Comparative Example 4
[0114] The method is the same as in Example 1, except that the first precursor is not modified in step (2); that is:
[0115] (2) Add 4 parts of concentrated hydrochloric acid (35wt%) to 10 parts of pure water in sequence, stir evenly, and prepare a control hydrochloric acid solution. The first precursor obtained in step (1) is put into 2 times the weight of the above control hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6 hours, and cooled to obtain a modified first precursor. Then, the modified first precursor and micron-sized iron oxide powder are mixed in a mass ratio of 1:0.5, heated to 950°C in a box furnace under a nitrogen atmosphere, kept warm for 2 hours, cooled to room temperature, and the obtained chemical reaction material, hydrochloric acid, and 60°C pure water are mixed in a certain ratio (1:0.5:3), stirred for 10 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor.
[0116] Comparative Example 5
[0117] The method is the same as in Example 1, except that in step (2), the first precursor is not subjected to chemical reaction modification; that is:
[0118] (2) Add 2 parts of hydrogen peroxide (31wt%) and 4 parts of concentrated hydrochloric acid (35wt%) to 10 parts of pure water in sequence, stir evenly, and prepare a 4.5wt% hydrogen peroxide hydrochloric acid solution. The first precursor obtained in step (1) is put into 2 times the weight of the above hydrogen peroxide hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6 hours, and cooled to obtain a modified first precursor. After that, the modified first precursor is heated to 950°C in a box furnace directly under a nitrogen atmosphere, kept warm for 2 hours, cooled to room temperature, and the obtained chemical reaction material, hydrochloric acid, and 60°C pure water are mixed in a certain ratio (1:0.5:3), stirred for 10 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor.
[0119] Comparative Example 6
[0120] The method is the same as in Example 1, except that in step (2), a strong base is used to replace the reaction additive to chemically modify the first precursor; that is:
[0121] (2) Add 2 parts of hydrogen peroxide (31wt%) and 4 parts of concentrated hydrochloric acid (35wt%) to 10 parts of pure water in sequence, stir evenly, and prepare a 4.5wt% hydrogen peroxide hydrochloric acid solution. The first precursor obtained in step (1) is put into 2 times the weight of the above hydrogen peroxide hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6 hours, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor and micro-particle potassium hydroxide powder are mixed in a mass ratio of 1:0.5, heated to 950°C in a box furnace under a nitrogen atmosphere, kept warm for 2 hours, cooled to room temperature, and the material obtained by the chemical reaction, hydrochloric acid, and 60°C pure water are mixed in a certain ratio (1:0.5:3), stirred for 10 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor; the schematic diagram of the pore structure of the second precursor is shown as follows Figure 4b As shown;
[0122] The first charge and discharge curve of the hard carbon material in this comparative example is as follows Figure 3 shown.
[0123] Comparative Example 7
[0124] The method is the same as that of Example 1, except that in step (2), the first precursor is not modified, and a strong base is used to replace the reaction additive to chemically modify the first precursor; that is:
[0125] (2) Add 4 parts of concentrated hydrochloric acid (35wt%) to 10 parts of pure water in sequence by mass, stir evenly, and prepare a control hydrochloric acid solution. The first precursor obtained in step (1) is put into 2 times the weight of the above control hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6 hours, and cooled to obtain a modified first precursor. Then, the modified first precursor and micro-particle potassium hydroxide powder are mixed in a mass ratio of 1:0.5, heated to 950°C in a box furnace under a nitrogen atmosphere, kept warm for 2 hours, cooled to room temperature, and the obtained chemical reaction material, hydrochloric acid, and 60°C pure water are mixed in a certain ratio (1:0.5:3), stirred for 10 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor.
[0126] Comparative Example 8
[0127] The method is the same as in Example 1, except that in step (2), water vapor is used instead of the reaction additive to chemically modify the first precursor; that is:
[0128] (2) Add 2 parts of hydrogen peroxide (31wt%) and 4 parts of concentrated hydrochloric acid (35wt%) to 10 parts of pure water in sequence, stir evenly, and prepare a 4.5wt% hydrogen peroxide hydrochloric acid solution. The first precursor obtained in step (1) is put into 2 times the weight of the above hydrogen peroxide hydrochloric acid solution, heated to about 60°C in a water bath under stirring, reacted for 6 hours, and cooled to obtain a modified first precursor. Thereafter, the modified first precursor is transferred to a rotary kiln, heated to 950°C under a nitrogen atmosphere, and water vapor is introduced with nitrogen as a carrier gas for 2 hours, and the water vapor is stopped and cooled to room temperature. The material obtained by the chemical reaction, hydrochloric acid, and 60°C pure water are mixed in a certain ratio (1:0.5:3), stirred for 10 hours, solid-liquid separation, washed to pH=5-6, and dried to obtain a second precursor; the schematic diagram of the pore structure of the second precursor is shown as follows Figure 4c As shown;
[0129] The first charge and discharge curve of the hard carbon material in this comparative example is as follows Figure 3 shown.
[0130] Comparative Example 9
[0131] The method is the same as in Example 1, except that in step (3), no second carbon source is used to compound with the second precursor; that is:
[0132] (3) The second precursor is placed in a nitrogen atmosphere and pre-carbonized at 600° C. in a box furnace for 0.5 h. Then, it is crushed by a jet mill to a median particle size of about 5 μm, and sieved through a 30-mesh sieve to obtain a second crushed material. Finally, the second crushed material is transferred to a box furnace, heated to 1200° C. in a nitrogen atmosphere and kept for 4 h, and naturally cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0133] Comparative Example 10
[0134] The method is the same as Example 1, except that in step (3), a carbon source with a high residual carbon rate is not used to compound with the second precursor; that is, "polystyrene" in step (3) is replaced by "sucrose".
[0135] Comparative Example 11
[0136] The method is the same as in Example 1, except that the high temperature sintering temperature used in step (3) is too high; that is:
[0137] Replace the medium- and high-temperature sintering conditions in (3) “1200°C for 4 h” with “1600°C for 4 h”.
[0138] Comparative Example 12
[0139] The method is the same as in Example 1, except that the high temperature sintering temperature used in step (3) is too low; that is:
[0140] Replace the medium- and high-temperature sintering conditions in (3) “1200°C for 4 h” with “1100°C for 4 h”.
[0141] The specific test method is described below:
[0142] (1) Raman D / G(w) test. Raman spectrum was tested using the Raman tester Horiba XploRA to test Raman D / G(w). The test conditions were He-Ne laser (wavelength 532nm), filter 10%, hole 500μm, slit 100μm, grating 1800gr / mm, exposure time 60s, accumulation times 2 times, microscope objective 50X Lwd, test range 800cm -1 ~2000cm -1 . D peak at 1350cm -1 Nearby, G peak at 1600cm -1 The D peak half-width and G peak half-width are obtained by Raman spectroscopy, and 20 points are randomly selected for testing and averaged to obtain the D peak half-width and G peak half-width of the material. The ratio of the D peak half-width to the G peak half-width of the material is Raman D / G(w).
[0143] (2) Specific surface area test. The specific surface area was obtained by nitrogen adsorption test at 77K using a Micrometer Spectrometer (model ASAP2460). The specific surface area was calculated using the BET formula (unit: m 2 / g).
[0144] (3) Median particle size test. MASTERSIZER3000 was used for the test. The particle refractive index was 2.42, the absorptivity was 1.0, the dispersant was water, and the dispersant refractive index was 1.33. The method was to weigh about 0.1 g of sample into a 100 mL beaker, add water to 50 mL, ultrasonicate for 1 min, add sample until the shading degree was 8-12%, and start internal ultrasonic test.
[0145] (4) Carbon interlayer spacing test. A Panalytical X'Pert PRO MPD tester was used, with Cu target Kα ray (wavelength λ = 0.1541 nm) as the light source, and XRD data were obtained in the 2Theta range of 10° to 90°. The carbon interlayer spacing was calculated by substituting the diffraction angle (002) of XRD into the Scherrer formula (unit: nm).
[0146] (5) 3T powder compaction density (g / cm 3 ). Shenzhen Sansi Zongheng Battery Powder Compaction Density Tester UTM7305 was used for testing. A sample of specified mass was placed in a mold and subjected to a pressure of 3.0T. The pressure was maintained for 30S and then released to 20N to test its thickness. According to the formula ρ=10*(m / S*H), the compaction density (unit: g / cm 3 ).
[0147] (6) Oil absorption test. The oil absorption value was tested using the Absorptometor C carbon black oil absorption meter produced by Brabender, Germany. The sample was added to the mixing chamber, and linseed oil was dripped into the sample in the mixing chamber at a constant rate while stirring at a constant speed. The viscosity of the mixture gradually increased and a peak value appeared. The oil absorption value (unit: mL / 100g) was calculated based on the amount of linseed oil dripped at 70% of the maximum torque.
[0148] (7) Conductivity test: The powder conductivity of the material was tested using Mitsubishi Chemical's MCP-PD51 tester. The sample was added and tested at 20KN to obtain the conductivity data (unit: S / cm).
[0149] (8) SEM photos. The samples were scanned using a Hitachi S4800 scanning electron microscope to obtain SEM photos.
[0150] (9) Button-type half-cell production and testing
[0151] The specific button cell electrode sheet is prepared by a method known in the art: the hard carbon material, the conductive agent and the binder are adjusted to a solid content of 50% with deionized water in a mass percentage of 91:3:6, and mixed evenly, coated on a copper foil current collector, vacuum dried at 110°C for 6 hours, and rolled to a surface density of 5.5±0.5mg / cm2 , punched into a disc using a 14 mm diameter puncher to obtain a negative electrode;
[0152] Button cell production: sodium sheet is used as the counter electrode, 1 mol / L NaPF6 / DIGLYME (100 Vol%) is used as the electrolyte, glass fiber is used as the diaphragm, and a 2032 button cell shell is used to assemble the button half cell.
[0153] The test conditions for the specific capacity and initial efficiency of the hard carbon negative electrode materials obtained in Examples 1-7 and Comparative Examples 1-12 are as follows: at room temperature (about 25°C), the Arbin battery test system is used for testing, firstly 0.1C constant current discharge to 1mV, then constant voltage discharge at 1mV to a current density of 3.5*10 -6 A, charging cut-off; after standing, then charging at 0.1C, cut-off voltage 2V, test results are shown in Table 2. Specific capacity (mAh / g) is the first charge capacity divided by the weight of the hard carbon negative electrode material contained in the negative electrode plate, the nominal specific capacity is 300mAh / g, the first efficiency is the ratio of the first charge capacity to the first discharge capacity.
[0154] Test of platform capacity and slope capacity: According to the charging data of the power-off test, the capacity value corresponding to the voltage of 0.12V is divided by the weight of the hard carbon negative electrode material contained in the negative electrode plate, which is the platform capacity. The slope capacity is the specific capacity minus the platform capacity.
[0155] (10) Finished battery production and testing:
[0156] The BNH-O3A layered oxide was used as the positive electrode. The positive electrode material: conductive agent: binder were mixed according to the mass percentage of 96%: 2%: 2%. They were adjusted to a solid content of 50% with NMP, coated on both sides of the aluminum foil, dried, and rolled to control the surface density to 300g / m 2 Around, get the positive electrode.
[0157] The hard carbon material, conductive agent and binder are mixed in a mass percentage of 91:3:6, adjusted to a solid content of 50% with deionized water, and evenly coated on a copper foil current collector, dried, and rolled to a surface density of 150 gg / m 2 About, the negative electrode sheet is obtained;
[0158] Assemble the soft pack battery with NP excess ratio of 20% for positive and negative electrodes, PP separator, 1M NaPF6 in EC∶DMC∶EMC=1∶1∶1 (volume ratio) as electrolyte, and test voltage range of 2-4V;
[0159] 6C / 0.2C rate charge retention rate (%): At room temperature, the divided battery was subjected to constant current charge and discharge tests at 0.2C / 0.2C and 6C / 6C respectively. The 6C charge capacity was divided by the 0.2C charge capacity to obtain the 6C / 0.2C rate charge retention rate (%);
[0160] 1C / 1C cycle 500-week retention rate (%): At room temperature, 1C / 1C constant current charge and discharge cycle test is adopted. The discharge capacity of the 500th week is divided by the discharge capacity of the first week to obtain the 1C / 1C cycle 500-week retention rate (%);
[0161] The test results of the above embodiments and comparative examples are shown in Table 1 and Table 2.
[0162] Table 1
[0163]
[0164]
[0165]
[0166] Refer to Table 1 to Table 2 and Figure 1 As shown in Figure 4, we can see the following:
[0167] The 3T powder of the sodium ion battery hard carbon negative electrode material of Examples 1 to 7 has a compaction density of up to 0.97g / cc~1.1g / cc, a specific capacity of 335mAh / g~416mAh / g, an initial efficiency of 89.1%~93.9%, a 6C / 0.2C charging capacity retention rate of up to 87.5%~91.9%, and a 1C / 1C@500 cycle retention rate of 87.8%~97.6%, showing excellent electrochemical performance. This shows that the hard carbon material provided by the present invention has the advantages of high compaction, high capacity, high initial efficiency, high rate and long cycle.
[0168] This is because the sodium ion battery hard carbon negative electrode material provided by the present invention has the characteristics of high graphite microcrystal crosslinking, many closed pores, high carbon matrix density and good conductivity. According to the pre-carbonized hard carbon material at a certain temperature, the present invention has the characteristics of interlaced distribution of crystallized carbon and amorphous carbon, and the reaction activity between amorphous carbon and modified solution and chemical modifier is stronger than that between crystallized carbon. The pre-carbonization is modified by modified solution to further improve the degree of difference in the reaction activity between amorphous carbon and crystallized carbon and chemical modifier. Through chemical reaction, the amorphous carbon in the first precursor is removed, so as to prepare a second precursor with high crystallized carbon content, uniform pore distribution, small pore size and high porosity. Then, the second carbon source is compounded, and the molecules of the second carbon source enter the pores of the hard carbon. After high-temperature sintering, the molecules of the second carbon source crosslink with the crystallized carbon, and the open pores are converted into closed pores, thereby obtaining a hard carbon negative electrode material with high three-dimensional crosslinking degree of graphite microcrystals of hard carbon, many closed pores, high carbon matrix density and good conductivity. The closed pores serve as active sodium storage sites and contribute to capacity performance; the high degree of three-dimensional cross-linking of graphite microcrystals and high conductivity are beneficial to improving the kinetic performance.
[0169] The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Example 1 are worse than those of the sodium ion battery hard carbon negative electrode material of Example 1. This is because the first pre-carbonization temperature of Comparative Example 1 is significantly higher than that of Example 1, resulting in a decrease in the amount of amorphous carbon in the first precursor and a reduction in active sites, which leads to the failure of modification and chemical modification, and the resulting second precursor has a high amorphous carbon component content and a high Raman D / G(w). During the high-temperature sintering stage, since amorphous carbon hinders the stereo cross-linking of crystallized carbon, the degree of stereo cross-linking of the graphite microcrystals of the hard carbon is small, the number of closed pores is small, the conductivity is poor, and the Raman D / G(w) is high. Therefore, there are fewer pore sodium storage sites, large sodium ion diffusion steric hindrance, and poor kinetic performance. The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the hard carbon negative electrode material are poor.
[0170] The 3T powder compaction density, specific capacity, first efficiency, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Example 2 are worse than those of the sodium ion battery hard carbon negative electrode material of Example 1. This is because the first pre-carbonization temperature of Comparative Example 2 is significantly lower than that of Example 1, resulting in the failure of the carbon skeleton of the first precursor to be fully formed, and the condition of "the staggered distribution characteristics of crystallized carbon and amorphous carbon" is not met, resulting in a lack of selectivity in the modification and chemical reaction modification of the carbon component. Therefore, the second precursor has a high content of amorphous carbon components and a high Raman D / G(w). At the same time, the carbon matrix is over-etched, the specific surface area and pore size become larger, and the generated large-aperture openings are still difficult to convert into closed pores after compounding the second carbon source and high-temperature sintering, and the degree of three-dimensional cross-linking of the graphite microcrystals of the hard carbon is low. The resulting hard carbon has a large specific surface area, low 3T compaction density, low conductivity, and high Raman D / G(w). Therefore, the specific capacity, first efficiency, and platform capacity of hard carbon materials are low, and the 6C / 0.2C capacity retention rate and 1C / 1C cycle 500-cycle retention rate are poor.
[0171] Comparative Examples 1 and 2 illustrate that the first pre-carbonization temperature should be neither too high nor too low, and it is necessary to control it within a suitable range.
[0172] The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Example 3 are worse than those of the sodium ion battery hard carbon negative electrode material of Example 1. This is because, in step (2) of Comparative Example 3, the first precursor is not modified and chemically modified, and the second carbon source is not compounded in step (3). It is explained that the modification, chemical modification, and compounding of the second carbon source in the hard carbon material preparation method provided by the present invention can improve the three-dimensional cross-linking degree of graphite microcrystals, increase the number of closed pores, and improve the conductivity while maintaining a high carbon matrix density, thereby improving the capacity, rate, and cycle performance of the hard carbon negative electrode material.
[0173] The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Example 4 are worse than those of the sodium ion battery hard carbon negative electrode material of Example 1. This is because, in step (2) of Comparative Example 4, the first precursor is not modified. Therefore, the difference in reaction activity between the amorphous carbon and crystallized carbon of the first precursor and the chemical modifier is small. After the chemical reaction stage, the amorphous carbon is not directionally removed. The amorphous carbon component content of the second precursor of the present invention is higher than that of Example 1, and the Raman D / G(w) is high. In the high-temperature sintering stage, since amorphous carbon hinders the crystallized carbon from undergoing stereo cross-linking, the degree of stereo cross-linking of the graphite microcrystals of the hard carbon is small, the number of closed pores is small, the conductivity is poor, and the Raman D / G(w) is high. Therefore, there are fewer pore sodium storage sites, the sodium ion diffusion steric hindrance is large, and the kinetic performance is poor. The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500 cycle retention rate of the hard carbon negative electrode material are poor, which shows that the modification in step (2) of the present invention is necessary to improve the electrochemical performance of hard carbon.
[0174] The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Example 5 are worse than those of the sodium ion battery hard carbon negative electrode material of Example 1. This is because, in step (2) of Comparative Example 5, the modified first precursor is not mixed with the reaction additive for reaction. In the present invention, there is only modification, and no mixing reaction with the reaction additive, and the amorphous carbon component of the hard carbon cannot be directionally removed. Therefore, the amorphous carbon component content of the second precursor of the present invention is higher than that of Example 1, and the Raman D / G(w) is high. During the high-temperature sintering stage, since amorphous carbon hinders the crystallized carbon from undergoing stereo cross-linking, the stereo cross-linking degree of the graphite crystallites of the hard carbon is small, the number of closed pores is small, the conductivity is poor, and the Raman D / G(w) is high. Therefore, there are fewer pore sodium storage sites, the sodium ion diffusion steric hindrance is large, and the kinetic performance is poor. The specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the hard carbon negative electrode material are poor. This indicates that the mixed reaction of modifying the first precursor and the reaction additive in step (2) of the present invention is necessary to improve the electrochemical performance of hard carbon.
[0175] The 3T powder compaction density, specific capacity, platform area capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Examples 6 and 8 are worse than those of the sodium ion battery hard carbon negative electrode material of Example 1. This is because, in step (2) of Comparative Examples 6 and 8, alkali (microparticulate potassium hydroxide) and gas-phase reactant (water vapor) are used to replace the reaction additive and react with the modified first precursor. This is because the reactivity of the alkali and the gas-phase reactant is too strong, and they are easy to react with both crystallized carbon and amorphous carbon without obvious selectivity. Therefore, the amorphous carbon of the second precursor cannot be removed in a direction, and its proportion is higher than that of Example 1, so the Raman D / G (w) is high. In addition, due to the strong reaction characteristics of the alkali and the gas-phase reactant, the carbon matrix is easily over-etched, the specific surface area and pore size become larger, and the generated large-aperture openings are still difficult to convert into closed pores after compounding the second carbon source and high-temperature sintering, and the degree of stereo cross-linking of the graphite microcrystals of the hard carbon is low. The obtained hard carbon has a large specific surface area, low 3T compaction density, low electrical conductivity, and high Raman D / G(w). Therefore, the specific capacity, initial efficiency, and platform capacity of the hard carbon material are low, and the 6C / 0.2C capacity retention rate and 1C / 1C cycle 500 week retention rate are poor. This shows that the reaction additive used in step (2) of the present invention is necessary for improving the electrochemical performance of hard carbon and is non-replaceable. It is worth noting that the 3T powder compaction density, specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500 week retention rate of the sodium ion battery hard carbon negative electrode material of Comparative Example 6 are better than those of Comparative Example 8. As shown in Figure 4, this is because, after the hard carbon reacts with an alkali, pores with (large pore size + small pore size) are formed, while after the gas phase reactant, pores with mainly large pore size are formed. Large pore size pores are difficult to transform into closed pores, and the density performance will be significantly sacrificed, while small pore size pores are easy to become closed pores without significantly sacrificing the density performance. The pores in Example 1 of the present invention are formed by selectively removing the amorphous phase in the second precursor, and have the characteristics of uniform distribution and small pore size. After compounding the second carbon source and high-temperature sintering, the graphite microcrystals undergo three-dimensional cross-linking, and the pores are converted into closed pores with sodium storage activity without sacrificing density performance. Therefore, the pore-forming method provided by the present invention has obvious technical advantages over the pore-forming modification of alkali and gas-phase reactants.
[0176] The 3T powder compaction density, specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material in Comparative Example 7 are worse than those of the sodium ion battery hard carbon negative electrode material in Example 1, and there is no significant difference with the sodium ion battery hard carbon negative electrode material in Comparative Example 8. This is because the only difference from Comparative Example 8 is that the first precursor is not modified in step (2) of Comparative Example 7. This shows that under the premise that step (2) uses alkali (microparticulate potassium hydroxide) respectively, the modification has little effect on the hard carbon structure and electrochemical properties. The reason why the 3T powder compaction density, specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material in Comparative Example 7 are worse than those of the sodium ion battery hard carbon negative electrode material in Example 1 is the same as that in Comparative Example 8.
[0177] The 3T powder compaction density, specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material in Comparative Example 9 are worse than those of the sodium ion battery hard carbon negative electrode material in Example 1. This is because the second precursor in step (3) of Comparative Example 9 is not compounded with the second carbon source. The role of the second carbon source in the method provided by the present invention is to undergo stereo cross-linking with the crystallized carbon of the hard carbon during high-temperature sintering, promote the conversion of open pores into closed pores, and improve the density performance of the hard carbon. Therefore, the conversion of open pores to closed pores in the hard carbon negative electrode material of Comparative Example 9 is insufficient, and some open pore structures remain, sacrificing density performance, with fewer pore sodium storage sites, large sodium ion diffusion steric hindrance, and poor kinetic performance. This shows that the compounding of the second precursor in step (3) of the present invention with the second carbon source is necessary to improve the electrochemical and compaction density performance of hard carbon.
[0178] The 3T powder compaction density, specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material in Comparative Example 10 are worse than those of the sodium ion battery hard carbon negative electrode material in Example 1. This is because, in step (3) of Comparative Example 10, the second precursor is compounded with a carbon source (sucrose) with a high carbon residue content. Carbon source molecules with a high carbon residue content mostly contain relatively large functional groups, which are difficult to enter the pore structure of the second precursor. Therefore, it is difficult to undergo a stereo cross-linking reaction with the crystallized carbon of the hard carbon during high-temperature sintering, and the effect of promoting the conversion of open pores into closed pores is not significant. Therefore, there are fewer closed pores and more open pores, the density performance is reduced, the conductivity is poor, the sodium ion diffusion steric hindrance is large, and the kinetic performance is poor. This shows that the type of the second carbon source used in step (3) of the present invention is irreplaceable.
[0179] The 3T powder compaction density, specific capacity, slope area capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material in Comparative Example 11 are worse than those of the sodium ion battery hard carbon negative electrode material in Example 1. This is because the temperature of the high-temperature sintering in step (3) of Comparative Example 11 is significantly higher than that in Example 1. Too high a high-temperature sintering temperature will lead to a decrease in the carbon layer spacing, a decrease in the interlayer intercalation sodium storage sites, and partial collapse of the closed pores, so the corresponding specific capacity, platform area capacity, and slope area capacity are reduced. The reduction in interlayer spacing leads to an increase in the sodium ion diffusion steric hindrance of the hard carbon material and a decrease in the kinetic performance, which leads to a decrease in the 6C / 0.2C capacity retention rate and the 1C / 1C cycle 500-week retention rate. The temperature of the high-temperature sintering used in step (3) of the present invention should not be too high.
[0180] The 3T powder compaction density, specific capacity, platform capacity, 6C / 0.2C capacity retention rate, and 1C / 1C cycle 500-week retention rate of the sodium ion battery hard carbon negative electrode material in Comparative Example 12 are worse than those of the sodium ion battery hard carbon negative electrode material in Example 1. This is because the temperature of the high-temperature sintering in step (3) of Comparative Example 11 is significantly lower than that in Example 1. Too low a temperature for high-temperature sintering will result in an insignificant effect on promoting the conversion of open pores into closed pores. Therefore, there are fewer closed pores and more open pores, and thus the corresponding specific capacity and platform capacity are reduced. At the same time, the electrical conductivity is poor, the sodium ion diffusion steric hindrance is large, and the kinetic performance is poor, resulting in a decrease in the 6C / 0.2C capacity retention rate and the 1C / 1C cycle 500-week retention rate. The temperature of the high-temperature sintering adopted in step (3) of the present invention should not be too low.
[0181] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0182] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A hard carbon negative electrode material for a sodium ion battery, characterized in that: The hard carbon negative electrode material for sodium ion battery is a hard carbon material cross-linked with graphite microcrystals, and the carbon layer spacing of the hard carbon negative electrode material for sodium ion battery is 0.37nm-0.40nm; the Raman D / G(w) value of the hard carbon negative electrode material for sodium ion battery is in the range of 1.1-1.6; the 3T powder compaction density of the hard carbon negative electrode material for sodium ion battery is 0.96g / em 3 -1.10g / em 3 .
2. The hard carbon negative electrode material for sodium ion battery according to claim 1, characterized in that: The Raman D / G(w) value of the hard carbon negative electrode material for sodium ion batteries is in the range of 1.2-1.5; And / or, the powder conductivity of the hard carbon negative electrode material for sodium ion battery is 36S / cm-42S / cm; And / or, the specific surface area of the hard carbon negative electrode material for sodium ion battery is 1.0m 2 / g-10.0m 2 / g; And / or, the oil absorption of the hard carbon negative electrode material for sodium ion battery is 48mL / 100g-58mL / 100g.
3. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: include: Performing a first pre-carbonization treatment on a first carbon source to obtain a first precursor; The first precursor is modified and then mixed with a reaction additive to obtain a second precursor; wherein the modification can at least enhance the reaction activity of amorphous carbon in the first precursor; And, the second precursor is mixed with a second carbon source and subjected to a second pre-carbonization treatment and a high-temperature sintering treatment to obtain a hard carbon negative electrode material for a sodium ion battery.
4. The preparation method according to claim 3, characterized in that: Specifically include: In an inert gas atmosphere or an oxygen-deficient atmosphere, a first carbon source is subjected to a first pre-carbonization treatment at 400° C. to 600° C., and then the obtained product is subjected to a first pulverization treatment to obtain a first precursor; Preferably, the inert atmosphere includes any one or more combinations of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere; preferably, the oxygen-deficient atmosphere includes a gas atmosphere with an oxygen content ≤1wt%.
5. The preparation method according to claim 4, characterized in that: The first carbon source includes any one or more combinations of plant carbon sources, sugar carbon sources, resin carbon sources, and polymer carbon sources; preferably, the plant carbon source includes any one or more combinations of coconut shells, almond shells, pistachio shells, macadamia shells, jujube shells, chestnut shells, hazelnut shells, peanut shells, walnut shells, peach shells, cotton, wood, bamboo, bagasse, straw, and lignin; preferably, the sugar carbon source includes any one or more combinations of sucrose, maltose, lactose, fructose, starch, and cellulose; preferably, the resin carbon source includes any one or more combinations of phenolic resins, polyimide resins, polyester resins, polyaldehyde resins, polyolefin resins, and polyacrylic acid resins; preferably, the polymer carbon source includes any one or more combinations of polyfurfuryl alcohol, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, natural rubber, and polyacrylonitrile; And / or, the first pre-carbonization treatment time is 0.5h-24h; And / or, the preparation method specifically comprises: using a pulverizing device to perform a first pulverizing treatment on the product obtained by the first pre-carbonization treatment until the median particle size is 1 μm-15 μm, and then sieving to obtain a first precursor.
6. The preparation method according to claim 3, characterized in that: Specifically include: Modifying the first precursor by liquid phase modification to obtain a modified first precursor; And, the modified first precursor is mixed with a reaction additive and reacted in an inert atmosphere at 500°C-1000°C for 0.5h-3h, and then purified and dried to obtain a second precursor; wherein the inert atmosphere includes any one or more combinations of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere.
7. The preparation method according to claim 6, characterized in that: The liquid phase modification comprises: mixing the first precursor with an oxidizing acid solution and reacting at 50° C.-100° C. for 0.5 h-24 h to obtain a modified first precursor; Preferably, the oxidizing acid solution comprises a solute and an acid, wherein the solute comprises any one or more combinations of potassium permanganate, potassium dichromate, potassium perchlorate, potassium hypochlorite, sodium permanganate, sodium dichromate, sodium perchlorate, sodium hypochlorite, and hydrogen peroxide; the acid comprises any one or more combinations of hydrochloric acid, hydrofluoric acid, phosphoric acid, sulfuric acid, and nitric acid; the concentration of the solute in the oxidizing acid solution is 0.1wt%-5wt%; preferably, the mass ratio of the first precursor to the oxidizing acid solution is 1:2-20; and / or, the mass ratio of the reaction additive to the modified first precursor is 0.05-2.0:1; And / or, the reaction additive includes any one or more combinations of iron oxide, ferrosoferric oxide, magnesium oxide, calcium oxide, zinc oxide, chromium oxide, silver oxide, niobium oxide, cobalt oxide, nickel oxide, and copper oxide.
8. The preparation method according to claim 3, characterized in that: Specifically include: The second precursor and the second carbon source are fully mixed, and then the obtained mixture is subjected to a second pre-carbonization treatment at 400°C-600°C in an inert atmosphere, and then the obtained product is subjected to a second pulverization treatment to obtain a second pulverized material; and the second pulverized material is subjected to high-temperature sintering at 1200°C-1500°C for 0.5h-10h in an inert atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery; wherein the inert atmosphere includes any one or more combinations of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere; Preferably, the second carbon source comprises a carbon source having a residual carbon rate lower than 15wt%; Preferably, the second carbon source comprises any one or more combinations of glucose, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyvinyl alcohol, epoxy resin, urea-formaldehyde resin, and melamine resin; Preferably, the mass ratio of the second carbon source to the second precursor is 0.03-0.3:1; Preferably, the second pre-carbonization treatment time is 0.5h-24h; Preferably, the preparation method specifically comprises: using a pulverizing device to perform a second pulverizing treatment on the product obtained by the second pre-carbonization treatment until the median particle size is 1 μm-15 μm, and then sieving to obtain a second pulverized material.
9. Use of the hard carbon negative electrode material for sodium ion battery according to claim 1 or 2 in the preparation of sodium ion batteries.
10. A negative electrode sheet for a sodium ion battery, characterized in that: Including the hard carbon negative electrode material for sodium ion battery as described in claim 8.
Citation Information
Cited By
Hard carbon material, preparation method thereof and sodium ion battery
CN119612499A
Hard carbon negative electrode material, preparation method thereof and sodium ion battery
CN120527363A
Preparation method of high-capacity hard carbon
CN122187007A